Instructional feedback effects on youth football players behavior during small-sided games - Folgado, Hugo (2020)
Objective: The aim of this study was to explore how different instructional feedback information, provided by a coach during a football small sided game (SSG) situation, influenced young players behavior during practice. Methods: Three different SSG, played in a 30x40m pitch for 6 minutes each with 5 players-a-side, including goalkeepers, were promoted during a U13 football teams’ practice. The 3 instructional conditions, played randomly in every practice were: no instruction, where a coach was present, but no instruction was provided to players; passing instruction, where the coach encourage players to pass the ball; shooting instruction, where the coach asked to players to shot at the goal. Players’ displacement was captured by individual GPS units and a video notational system was used to capture players’ technical actions – passes, dribbles, shots. By merging both sources of information, the spatiotemporal information of the technical actions was computed. Results: With generally small effects, results showed a trend for a higher number of actions in both the passing and shooting instruction conditions, compared to the no instruction. Players shot more, closer to the goal and within a closer range of the opponents in the shooting condition. In the passing condition players passed more overall and more forward passes. Conclusions: Results indicate an influence of coaches’ instructions over players behavior during SSG practice. These instructions seem to demote players from an exploratory behavior during practice.